HUET training in Amelia, Louisiana. May 20th, 2013 Tidewater paid for cadets to take Huet training, in which someone was strapped into a body of a helicopter. As the helicopter was submerged, it flipped upside down and participates had to escape while underwater. - Edmiston, Brian
CSUM Cruise 2013